Changing perspectives on terrestrial nitrogen cycling: The importance of weathering and evolved resource‐use traits for understanding ecosystem responses to global change. (17th June 2019) - Wooliver, Rachel; Pellegrini, Adam F. A.; Waring, Bonnie; Houlton, Benjamin Z.; Averill, Colin; Schimel, Joshua; Hedin, Lars O.; Bailey, Joseph K.; Schweitzer, Jennifer A.
Abstract: Our understanding of terrestrial nitrogen (N) cycling is changing as new processes are uncovered, including the sources, turnover and losses of N from ecosystems. We integrate recent insights into an updated N‐cycling framework and discuss how a new understanding integrates eco‐evolutionary dynamics with nutrient cycling. These insights include (a) the significance of rock weathering as a biologically meaningful N source to plants and microbes; (b) the lack of consistent N limitation of organic matter decomposition by soil microbes; (c) species‐specific variation in plant N limitation; and (d) how fire effects on soil N shift with ecosystem properties. Using an eco‐evolutionary framework and revised knowledge of N cycling, we describe how (a) rock N weathering could have contributed more strongly to gradients in soil N availability than previously recognized, (b) evolution and co‐evolution of plant and soil microbial resource‐use traits underlie whether decomposition and production are N‐limited, and (c) the effects of fire on soil N pools are mediated by composition of plant species and time‐scale. Our revised framework of N cycling provides a way forward for improving biogeochemical models to more accurately estimate rates of plant production and decomposition, and total soil N. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.